Diet preferences and reproduction of translocated barn owl, Tyto alba javanica in captivity - Zainal Abidin, Cik Mohd Rizuan; Mohd Noor, Hafidzi; Hamid, Noor Hisham; Salim, Hasber (Malaysian Palm Oil Board, 2017)
Five non-paired-translocated wild caught barn owl (Tyto alba javanica) transferred from Jerantut, Pahang in Peninsular to Lahad Datu in Sabah, Malaysia were tested for diet preference by size, and species and fecundity in captivity. Testing was done in flight cages where owls were free to select from a combination of three local rodent species distinguished into two size categories; large and small. Jacobs’ index confirmed that smaller rats were taken in greater numbers and took the shortest number of days to 100% consumption at Day 5 than larger ones. Preference for body parts consumed varied according to diet size and species. In the same period as the prey preference study, two females reproduced twice ranging from intervals of 44 to 63 days with an average clutch size of 6.8 eggs. Hatching rates ranged from 0% to 83% and fledging rates ranged from 0% to 75%. These results may have practical importance in the propagation of barn owls in their new environment as they will be exposed to different prey in terms of species and size range.